Interreligious Communication for Building Tolerance Between Muslim and Christian Communities in Bengkulu - Kurniawan, Siroy; Firmansyah Rahman Hakim, Uky; Muzzaky, Rois (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2024)
Inter-religious communication is a process of dialogue between religions to find common ground between adherents of these religions, so that an understanding can be created to live in harmony and peace. This study aims to explain the Muslim and Christian communities in viewing differences, as well as the communication process of Muslim and Christian communities, as well as communication barriers that occur between the two. This research uses a qualitative approach to explore data in depth, with a snackball sampling technique in determining the subject, and data collection through interviews, observation, and documentation. The results showed three main findings. First, Muslim and Christian communities uphold tolerance, respect each other in worship, although there are variations in attitudes such as fanaticism among Muslims. Second, interfaith communication begins with dialogue between religious leaders who teach tolerance, followed by community dialogue with open communication, empathy, and respect, including nonverbal messages such as facial expressions and touch. The communication process involves linear, secular, transactional and religious models. Third, communication barriers include attribution error, stereotyping, social prejudice, ethnocentrism, and value differences. This research contributes academically in studying interfaith communication as an effort to build tolerance between Muslim and Christian communities through dialogue and strengthening the value of diversity.